Determinants of long-term unemployment in early adulthood: A Finnish birth cohort study - Tea Lallukka; Martta Kerkelä; Tiina Ristikari; Marko Merikukka; Heikki Hiilamo; Marianna Virtanen; Simon Øverland; Mika Gissler; Jaana I. Halonen (Elsevier, 2019)
Cumulative contributions of social and health-related determinants to long-term unemployment during early working life among young adults are poorly understood. Therefore, we used four cumulative indices of both parental and own social and health-related determinants of such unemployment among a cohort which comprised a complete census of children born in Finland in 1987. The cohort participants were registered in the Medical Birth Register, and they were followed-up through 2015 (N = 46 521). We calculated predicted probabilities for long-term unemployment (> 12 months) when participants were 25-28 years. Moreover, we examined whether the associations differed by unemployment at the municipal level.During the follow-up, 4.5% of women and 7.1% of men experienced long-term unemployment. All cumulative indices of parental and own social and health-related determinants predicted the probability of long-term unemployment. The greatest probabilities were observed for own social determinants, both in municipalities with high and low unemployment although the probabilities were higher in the high-unemployment municipalities. Of the individual determinants, poor school performance showed the strongest association with long-term unemployment among women (OR 6.65, 95% CI 5.21-8.55) and men (OR 3.70, 95% CI 2.96-4.67), after adjusting for other own social determinants. The results highlight the importance of life course social equality in the prevention of long-term unemployment in early adulthood. Keywords: Social determinants, Psychiatric diagnoses, Teen-age pregnancies, School performance, Register-based, Child protection action